Analysis of Factors of Utilization of JKN Program Services in Pancur Batu District - Salsabila, Rizka Fauziah; Adelia, Difa; Gurning, Fitriani Pramita (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
The JKN program in Pancur Batu District, Deli Serdang Regency, has not been running optimally, with a low number of participants utilizing health services. This is due to various factors, including access, service quality, and public understanding. This study aims to identify the relationship between factors that influence the utilization of health services in the area. The method used is a quantitative approach with a cross-sectional design, involving 97 respondents selected by simple random sampling. Data were collected through questionnaires and analyzed using chi-square analysis. The results showed a significant correlation between the use of JKN services and education level (p = 0.015), availability of facilities and infrastructure (p = 0.009), accessibility (p = 0.002), and complaints of illness (p = 0.011). In contrast, no significant correlation was found between employment status (p = 0.805) and salary (p = 0.622) with service utilization. The conclusion of this study is that increasing the utilization of the JKN program requires a holistic approach, which includes improving access to health facilities, improving service quality, and educating the public about the benefits of the JKN program.